QUANTITATIVE EXPRESSION OF PROPOSED PRICE CONTROL MODEL OF CZECH POST - Svadlenka, Libor (Doprava a spoje, 2005)
The paper concretizes the principles of effective price control of Czech Post defined in the paper "Proposal of the Effective Price Control of Czech Post" presented on PERNER'S CONTACT 2004. This paper describes proposed model of price control outgoing from price-cap and tariff formula RPI-X and concentrates on its quantitative expression. Application of proposed model is carried out both for hypothetical period in past (in order to compare with the current control system) and for current control period in order to set relevant maximum price increase of regulated tariff basket (letter items)